2008
DOI: 10.1542/peds.2007-3237
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Care for Common Pediatric Respiratory Illnesses in United States Emergency Departments: Analysis of 2005 National Hospital Ambulatory Medical Care Survey Data

Abstract: Physicians treating children with asthma, bronchiolitis, and croup in US emergency departments are underusing known effective treatments and overusing ineffective or unproven therapies and diagnostic tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 35 publications
6
73
1
Order By: Relevance
“…3 With the use of pediatric specific ED quality measures and National Hospital Ambulatory Medical Care Survey (NHAMCS) data, we have reported on the 2005 US ED performance for the care of children with asthma, bronchiolitis, and croup. 2 In that study we found a high rate of use of radiographs in children who present to EDs with these illnesses.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…3 With the use of pediatric specific ED quality measures and National Hospital Ambulatory Medical Care Survey (NHAMCS) data, we have reported on the 2005 US ED performance for the care of children with asthma, bronchiolitis, and croup. 2 In that study we found a high rate of use of radiographs in children who present to EDs with these illnesses.…”
Section: Discussionmentioning
confidence: 73%
“…1 Three of the most common pediatric respiratory illnesses, asthma, bronchiolitis, and croup, account for nearly 1 million ED visits each year. 2 Practice variation in US EDs has been previously reported for bronchiolitis. 3 With the use of pediatric specific ED quality measures and National Hospital Ambulatory Medical Care Survey (NHAMCS) data, we have reported on the 2005 US ED performance for the care of children with asthma, bronchiolitis, and croup.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Recent studies have suggested the importance of measuring efficient use of resources for common pediatric ED conditions. 18,19 Efforts to streamline resource use by standardizing practice through evidence-based guidelines have been ongoing, but significant degrees of variation in practice remain. 4,5,19 Current ED quality measures do not include measures of efficient use of resources or how they correlate with ED outcomes.…”
mentioning
confidence: 99%
“…Consequently, interventions that are not efficacious and potentially harmful may be prescribed, whereas interventions that truly are efficacious may be withheld. [1][2][3][4][5] Positive trends in pediatric research have been observed since the first trial was published in 1948. Specifically, there has been a substantial increase in the number of trials published over time, the proportion of randomized to nonrandomized controlled trials, and the proportion of child to adult trials.…”
mentioning
confidence: 99%